DINASTI THULUNIYAH SANG PEMBANGUN PERADABAN DI MESIR - Alif Rohmah Nur Habibah; Mukarromah (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2022)
The Thulunid dynasty was the earliest manifestation of the political crystallization of the uncontrolled Turkish element at that time. the sudden emergence in the heart of the caliphate of the Abbasid dynasty was the beginning of the emergence of other minor dynasties of Turkic descent. The figure of Ahmad Ibn Thulus is a typical example of the founders of small dynasties who built their countries on the ruins of the caliphate. This dynasty was separate from the central government of Baghdad or only related to the name of the caliph in Baghdad. Much progress could be made by the Thulus dynasty even though it was short lived. The purpose of writing this scientific paper is to find out how the government of the Thuluniyyah dynasty and its contribution to the development of Islamic civilization and how the causes of the destruction of the dynasty. The analytical method used in this research is descriptive qualitative using literature study. The results of this study are that the Thulusan dynasty was a dynasty that was only 38 years old, many contributions could be made from various midwives such as territorial expansion, establishment of military grades, the field of architecture which was very luxurious and magnificent but the destruction of the Thuluniyah dynasty was due to the lack of a national base in the land they controlled so short-lived.